2022
DOI: 10.1186/s13058-022-01569-1
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Gla protein (MGP), GATA3, and TRPS1: a novel diagnostic panel to determine breast origin

Abstract: Background Metastatic breast carcinoma is commonly considered during differential diagnosis when metastatic disease is detected in females. In addition to the tumor morphology and documented clinical history, sensitive and specific immunohistochemical (IHC) markers such as GCDFP-15, mammaglobin, and GATA3 are helpful for determining breast origin. However, these markers are reported to show lower sensitivity in certain subtypes, such as triple-negative breast cancer (TNBC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 72 publications
4
21
1
Order By: Relevance
“…TRPS1 is a highly specific marker for breast origin tumours, especially in triple-negative breast cancer compared with GATA3. [20][21][22] In this study, we found that TRPS1 immunoreactivity in all cases was superior to GATA3 immunostaining and supported a breast origin, which could aid in routine clinical practice. Further studies are needed to better understand the role of TRPS1 in the development and progression of BMCAs and to explore the potential for targeted therapies.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…TRPS1 is a highly specific marker for breast origin tumours, especially in triple-negative breast cancer compared with GATA3. [20][21][22] In this study, we found that TRPS1 immunoreactivity in all cases was superior to GATA3 immunostaining and supported a breast origin, which could aid in routine clinical practice. Further studies are needed to better understand the role of TRPS1 in the development and progression of BMCAs and to explore the potential for targeted therapies.…”
Section: Discussionsupporting
confidence: 67%
“…TRPS1 is a highly specific marker for breast origin tumours, especially in triple‐negative breast cancer compared with GATA3 20–22 . In this study, we found that TRPS1 immunoreactivity in all cases was superior to GATA3 immunostaining and supported a breast origin, which could aid in routine clinical practice.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Du et al have also analysed several subsets of breast carcinomas with TRPS1, and found that altogether, only 8% of 1201 breast carcinomas were completely negative for this marker, and further 13% were weakly positive (≤ 10% staining, i.e., negative according to our criteria) [ 37 ]. In contrast to the previously cited studies, metaplastic carcinomas were those that showed the highest positivity rate (129/140, 92% demonstrating over 10% staining), and non-metaplastic TNBCs being the less frequently positive (in 69% of 144 cases).…”
Section: Discussionmentioning
confidence: 99%